2019
DOI: 10.1002/aelm.201900552
|View full text |Cite
|
Sign up to set email alerts
|

Ta Doping Enhanced Room‐Temperature Ferromagnetism in 2D Semiconducting MoTe2 Nanosheets

Abstract: Room temperature ferromagnetic semiconductors remain one of the most puzzling issues to be solved in tens of years. Nowadays, 2D ferromagnetic transition metal dichalcogenides (TMDCs) nanosheets attract continuous interest due to their exceptional electronic structure and properties. Here, it is identified that semiconducting 2H‐phase MoTe2 few/mono‐layer mixed nanosheets present a room temperature ferromagnetic property with Curie temperature above 400 K, although the MoTe2 bulk counterpart shows diamagnetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 55 publications
2
31
0
2
Order By: Relevance
“…Figure b shows the typical XRD results of our grown pristine and Cr-doped 2H-MoTe 2 single crystals. Clearly, all of the four samples were verified to exhibit only four prominent peaks (00L) in the range of 10–55°, which are well consistent with the standard hexagonal 2H-MoTe 2 (PDF# 73-1650), thus implying their good crystalline quality . As a comparison, the (002) peak gradually shifted to a lower diffraction angle with the increase of Cr dopants for Cr-doped 2H-MoTe 2 and the peak width did not change significantly (see the right panel of Figure b), indicating the larger lattice spacing after Cr doping.…”
Section: Results and Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Figure b shows the typical XRD results of our grown pristine and Cr-doped 2H-MoTe 2 single crystals. Clearly, all of the four samples were verified to exhibit only four prominent peaks (00L) in the range of 10–55°, which are well consistent with the standard hexagonal 2H-MoTe 2 (PDF# 73-1650), thus implying their good crystalline quality . As a comparison, the (002) peak gradually shifted to a lower diffraction angle with the increase of Cr dopants for Cr-doped 2H-MoTe 2 and the peak width did not change significantly (see the right panel of Figure b), indicating the larger lattice spacing after Cr doping.…”
Section: Results and Discussionsupporting
confidence: 52%
“…However, most ferromagnetic semiconductors are blocked by the low Curie temperature ( T c ) or serious incompatibility with existing semiconductor integration technologies. More recently, a series of two-dimensional (2D) van der Waals (vdW) layered materials have gradually emerged, which are appealing for spintronics. The intrinsic ferromagnetism has been found in bulk and exfoliated Cr 2 Ge 2 Te 6 and CrI 3 semiconductors, while their Curie temperatures are quite low (CrI 3 : bulk 61 K, monolayer 45 K; Cr 2 Ge 2 Te 6 : bulk 68 K, bilayer 30 K), which are far below room temperature of 300 K. On the other hand, 2D vdW layered transition-metal dichalcogenides (TMDCs) such as MoS 2 , MoSe 2 , MoTe 2 , and WS 2 have displayed potential in spintronics owing to their strong SOC and tunable band gaps within the 1–2 eV range. , Among the TMDCs, MoTe 2 shows several outstanding properties including variable polymorphism, small band gap, and strong SOC, while the intrinsically nonmagnetic feature limits its further applications in spin-related devices . However, experimentally, only defect-induced, nonintrinsic poor ferromagnetism with weak and negligible magnetic moment has been found in MoTe 2 so far. …”
Section: Introductionmentioning
confidence: 99%
“…Doping 2D nonmagnetic materials with magnetic atoms is an alternative route to induce magnetism in the material. It has been theoretically and experimentally demonstrated that robust ferromagnetic ordering can be achieved in 2D TMC systems (e.g., MoS 2 , MoTe 2 , WS 2 , WSe 2 , and SnS 2 ) through the substituted doping of transition metal atoms (e.g., V, Cr, Mn, Fe, Co, Ti, Ta, and Ni) 37,38,90–97 . In particular, room‐temperature ferromagnetism has been observed in ML V‐doped MoTe 2 , 93 Co‐doped MoS 2 , 95 V‐doped WSe 2 37,38 and V‐doped WS 2 , 97 resulting in dilute magnetic semiconductors.…”
Section: D Tmcs With Extrinsic Ferromagnetismmentioning
confidence: 99%
“…For the nonmagnetic‐doping induced magnetic ordering, our group [ 191 ] reported that Ta doped few/mono‐layer 2H MoTe 2 nanoplates exhibit a room‐temperature ferromagnetic property ( T C > 400 K). The fundamental reasons for such room‐temperature ferromagnetism are the combination of structural defects, including amorphous imperfections, disorders, and Te vacancies, as well as the edge‐states resulted from the reduced dimensionality.…”
Section: Physical Propertiesmentioning
confidence: 99%